2010
DOI: 10.1680/ensu.2010.163.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate drainage systems for a changing climate

Abstract: Sustainable drainage systems are increasingly seen as a better way of draining urban areas, being ‘more natural’, less resource intensive and offering water quantity and quality control with amenity benefits. Sustainable drainage systems ‘greening’ can also reduce heat island effects. However, little attention has been given to assessing the real value and sustainability of the approach and uncertainties remain over performance and robustness, as well as ownership and maintenance. Received wisdom suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…(FARAM et al, 2010); o uso de tubulações de maior diâmetro para suportar vazões maiores poderá diminuir a velocidade de escoamento nos períodos secos e causar problemas de acúmulos de sedimentos; caso a intensidade e frequência das chuvas fortes continuem a aumentar, as ampliações nos sistemas de drenagem poderão demandar novas intervenções no futuro, significando mais gastos e novas obras.…”
Section: Tr a N Siç ãO Em Inf R Ae S T R U T Ur A S Ur Ba Na S De C Ounclassified
See 1 more Smart Citation
“…(FARAM et al, 2010); o uso de tubulações de maior diâmetro para suportar vazões maiores poderá diminuir a velocidade de escoamento nos períodos secos e causar problemas de acúmulos de sedimentos; caso a intensidade e frequência das chuvas fortes continuem a aumentar, as ampliações nos sistemas de drenagem poderão demandar novas intervenções no futuro, significando mais gastos e novas obras.…”
Section: Tr a N Siç ãO Em Inf R Ae S T R U T Ur A S Ur Ba Na S De C Ounclassified
“…Além dos impactos previstos, os estudos analisados, reforçados por outras pesquisas (FARAM et al, 2010;MAILHOT;DUCHESNE, 2010;SCHOLZ;YANG, 2010;WATERS et al, 2003), reconhecem a importância do planejamento urbano a longo prazo, a ser pensado, desde já, como estratégia fundamental para evitar maiores transtornos quanto à drenagem num futuro não muito distante. Sugerem, também, ao considerar os investimentos elevados -necessários para adaptar os sistemas convencionais aos cenários previstos -, que técnicas alternativas e mais naturalizadas de condução, retenção e infiltração das águas de chuva podem ser empregadas como soluções complementares para mitigar o problema.…”
Section: N Ew T On C Elio B Ec Ker M Our a Paulo Renat O M E S Qui unclassified
“…There is a growing trend towards managing water in a more sustainable way by activating its natural behaviors and process in the urban environment [19][20][21]. Unlike conventional drainage focusing on the "end-of-pipe" or "at the point of the problem" solutions [22], with small and decentralized techniques, sustainable drainage systems can largely alleviate the adverse impacts of non-point source pollution to urban water bodies [10,23,24]. Such solutions rely on local treatment, retention, re-use, infiltration and conveyance of water runoff in urban areas and thus are in better agreement with sustainable principles [19,25].…”
Section: Introductionmentioning
confidence: 99%
“…The other briefings include topical information on carbon critical design (Clarke, 2010); Engineering Council guidance on Sustainability (Bogle, 2010); new geogrid technology for ground stabilisation (Dixon and Hall, 2010); and green IT Infrastructure (Sudworth, 2010). The papers cover: how low-carbon housing design is being informed by research (Gillott et al, 2010); how bridges may be delivered sustainably to help tackle climate change (Zhang, 2010); how climate change impacts on-demand irrigation systems (Daccache and Lamaddalena, 2010); and the place of appropriate drainage systems for tackling a changing climate (Faram et al, 2010).…”
mentioning
confidence: 99%
“…Much of this is now being badged as green infrastructure (GI). Significant efforts are now being made to evaluate in financial terms the added-value of LID or GI as an alternative or complement to traditional piped system drainage (Wise et al, 2010) also identified in this issue by Faram et al, (2010). Wise et al, (2010) identify the value of urban forests in: stormwater retention; reducing demand for energy for cooling and heating; reducing negative health impacts from extreme heat events; air quality improvements; and carbon dioxide reductions (avoided and sequestered).…”
mentioning
confidence: 99%